If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4) = x + -6 Reorder the terms: 3(4 + x) = x + -6 (4 * 3 + x * 3) = x + -6 (12 + 3x) = x + -6 Reorder the terms: 12 + 3x = -6 + x Solving 12 + 3x = -6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 12 + 3x + -1x = -6 + x + -1x Combine like terms: 3x + -1x = 2x 12 + 2x = -6 + x + -1x Combine like terms: x + -1x = 0 12 + 2x = -6 + 0 12 + 2x = -6 Add '-12' to each side of the equation. 12 + -12 + 2x = -6 + -12 Combine like terms: 12 + -12 = 0 0 + 2x = -6 + -12 2x = -6 + -12 Combine like terms: -6 + -12 = -18 2x = -18 Divide each side by '2'. x = -9 Simplifying x = -9
| 3u-53=2u | | 5(x-20)=x-8 | | 32=1/2b(4) | | 5x+24=x-32 | | 125=b+84 | | 1-6x=2-7x | | 3p+51=9p-45 | | 4(4-6)=7y | | 8x+45=3x | | 30x-6y=42 | | -7a=-12a | | 0.4x+50=1.6x+20 | | 3+3-3= | | 3p-30=102 | | 10u+66=5u+91 | | ×-3/×=2/5 | | tanx=0.009 | | 3x^2-16-16=0 | | y=4/5x-3;(-7,-2) | | 2b=8-8b | | y=-3+(10-1)(-12) | | y=-3+(8-1)(-12) | | y=-3+(3-1)(-12) | | 8z-26+6z-50+2z+5z-50+60+31+z+43=360 | | 4u+u+7+31+2u+2u-1+86+2u-16=360 | | 2x+y=17+2(x+2y) | | 6q-18+40+7q-24+20q-38+41+95=360 | | 2c+2c-32+30+2c+2c-46+32+32+2c=360 | | -4(-6x-y+9)= | | 13s-46+2s+15+s+23+7s+29+11s+s+24=360 | | 3m+2n^3= | | -4(-6-y+9)= |